GEOLOGICAL/GEOTOURIST OBJECTS OF THE TRANSCARPATHIAN REGION AS A REFLECTION OF THE GEOLOGICAL HISTORY OF THE CARPATHIANS - Hnylko, O.; Shevchuk, V.; Bozhuk, T.; Bogdanova, М.; Hnylko, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Сonsideration is given to description of important geological objects (observation points) of the southern slope of the Carpathians as reflections of sedimentary, paleogeographic and paleogeodynamic history of the Carpathians formation. Method. Standard method of geological description of outcrops, elements of sedimentological analysis of structural and textural features of rocks, and micropaleontological method are used. Results. A number of key geological objects that reflect the important stages of the geological evolution of the Carpathians in the Transcarpathian region near highways is described. These objects (the observation points in the article) can be represented as geotourist ones. In the first location which is in Yablunytsa Pass, an outcrop of Oligocene "striped" Holovets Limestone; further, along the Trostyanets Stream – Jurrassic pillow-lavas in the front of the Burkut Nappe; along the Kamyanyi Potik Stream – Jurassic- Early Cretaceous volcanogenic-sedimentary succession of the Kamyanyi Potik Nappe; along the Kosivka River – Eocene marls of the Marmarosh Massif sedimentary cover and the Inner Carpathian flysch of the Monastyrets Nappe; in the area of Novoselytsya village in the basin of the Luzhanka River – the Jurassic-Paleogene deposits of the Pieniny Klippen Belt; along the riverbed Tereblya in Zabrid village – Cretaceous-Paleogene deposits of the Marmarosh Klippen Zone are traced. Scientific novelty. The characteristic of a number of geological objects of the Transcarpathian region is supplemented and detailed and their brief description as reflections of sedimentary, paleogeographic and paleogeodynamic history of the Carpathians is presented. These objects reflect subsequent geological events: the birth of the Carpathian sedimentary basin; the formation of sub-oceanic and oceanic crust of the Outer Carpathian Flysch Basin; the formation of Inner Eastern Carpathian nappes and their destruction due to the formation of Early Cretaceous olistostrome of the Maramorosh Klippen Zone; ForeMarmarosh and Pieniny Klippen Belt accretionary prisms growing; and the final Oligocene stage of the Outer Carpathian Basin development. In addition, the range of Paleocene-Eocene paleogeographic elements such as (from the East to the West): (a) the passive margin of the Tisza-Dacia – (b) the deep-water Inner Carpathian Flysch Basin – (c) the Pieniny active edge of the Alcapa Terrane is demonstrated. The route of the geological tour described in the article is recommended to get acquainted with the main features of Geology, Geodynamics and processes of formation of the Carpathians. It can be used for further development of geotourism in the Carpathians.
Keywords: Ukrainian Carpathians; geotourism; flysch basin; accretionary prism; Tisza-Dacia; Alcapa